The effect of age and gender on the genetic regulation of serum 25-hydroxyvitamin D - the FIN-D2D population-based study. Issue 178 (April 2018) - Miettinen, Maija E.; Smart, Melissa C.; Kinnunen, Leena; Keinänen-Kiukaanniemi, Sirkka; Moilanen, Leena; Puolijoki, Hannu; Saltevo, Juha; Oksa, Heikki; Hitman, Graham A.; Tuomilehto, Jaakko; Peltonen, Markku
Highlights: Vitamin D status (serum 25OHD) is partly dependent on inherited factors. We studied if the genetic determinants of serum 25OHD are age and gender-dependent. Genetic regulation of serum 25OHD was weaker among older than younger adults. Abstract: In addition to sunlight and dietary sources, several genes in the metabolic pathway of vitamin D affect serum 25-hydroxyvitamin D (25OHD) concentration. It is not known whether this genetic regulation is influenced by host characteristics. We investigated the effect of age and gender on the genetic regulation of serum 25OHD concentration. In total, 2868 Finnish men and women aged 45–74 years participated in FIN-D2D population-based health survey in 2007. Of the 2822 participants that had serum 25OHD concentration available, 2757 were successfully genotyped. Age and gender-dependent association of SNPs with serum 25OHD concentration was studied in 10 SNPs with previously found association with vitamin D metabolites. Associations of 3 SNPs with serum 25OHD concentration were dependent on age with greater effects on younger (≤60 y) than older (>60 y) adults (rs10783219 in VDR, rs12512631 in GC and rs3794060 in NADSYN1/DHCR7; p interaction  = 0.03, 0.02 and 0.01, respectively). The results suggested a novel association between serum 25OHD concentration and rs8082391 in STAT5B gene in men but not in women ( p interaction  = 0.01). After multiple testing correction with false discovery rate method, two age-dependent interactions (rs3794060 in NADSYN1/DHCR7 gene and rs12512631 in GC gene) remained statistically significant. This is the first study to suggest that genetic regulation of serum 25OHD concentration is age-dependent. Our results also indicated a novel association between serum 25OHD concentration and SNP in STAT5B gene in men. The results need to be confirmed in future studies preferably in a larger sample.